Effects of long-term supplementation of bovine colostrum on iron homeostasis, oxidative stress, and inflammation in female athletes: A placebo-controlled clinical trial - Cieslicka, M.; Ostapiuk-Karolczuk, J.; Buttar, H. S.; Dziewiecka, H.; Kasperska, A.; Skarpanska-Stejnborn, A. (Nutrients, 2023)
Bovine colostrum supplementation has been suggested as a potential factor in reducing oxidative stress and inflammation. The primary objective of this study was to evaluate the effects of six months of bovine colostrum supplement intake (3.2 g; four capsules/day) in highly trained female athletes on changes in oxidative stress level, inflammation, and iron metabolism biomarkers after intense exercise. In this study, 20 trained female athletes were recruited. Participants were divided into two groups: 11 in the bovine colostrum (6-month supplementation) and 9 in the placebo group (6-month placebo supplementation). All participants completed an intense exercise test at the beginning of the experiment and after six months post-treatment. Blood samples were taken before, following exercise, and after 3 h recovery. Compared to the placebo group, the colostrum group showed a significant decrease in TBARS level (p< 0.01) at all time points, whereas a marked increase was observed in IL-6 (p < 0.01; pre-exercise) and SOD activity (p < 0.01), and transferrin (p < 0.01; rest period) and lactoferrin (p < 0.05; post-exercise) levels. The results suggested that 6-months of bovine colostrum supplementation is beneficial in the reduction of the harmful effects produced by free radicals (ROS), oxidative stress, and inflammation. In consequence, alleviation of the inflammatory response by bovine colostrum supplementation may also cause positive action on iron homeostasis in female athletes.